Precise control of the degree and regioselectivity of functionalization in nitro- and amino-functionalized di(trispyrazolylborato)iron(ii) spin crossover complexes. Issue 48 (30th November 2021) - Ma, Chenyang; Besson, Claire
Abstract : Di(trispyrazolylborato)iron(ii ) spin-crossover complexes with a tunable degree, nature and position of functionalization can be obtained via pyrazole exchange. Abstract : Di(trispyrazolylborato)iron(ii ) ([Tp2 Fe]) complexes represent one of the most robust classes of spin-crossover complexes. Their stability renders them particularly suitable for integration in nanoscale devices, e.g. as sensors or information storage units. While prior studies of the functionalization of those derivatives have been focused on the electronic and steric effects of alkyl and –CF3 groups in position 3, a pyrazole exchange reaction between nitropyrazole and either trispyrazolylborate or its iron complex allows the regioselective installation of nitro substituents in positions 3, 4 and 5 of the [Tp2 Fe] complexes. The degree of substitution can be varied from 1 to 4 functionalized pyrazoles per complex. The amine-functionalized analogues are accessed by reduction of the nitro analogues under hydrogen transfer conditions. With the exception of di- and tetra-3-NO2 substituted complexes, all derivatives display spin crossover properties in the solid state, with transition temperatures ranging from 180 to 380 K and showing different degrees of abruptness but no hysteresis. The Slichter–Drickamer model was used to extract the empirical thermodynamic transition parameters, allowing a systematic investigation of the influence of stoichiometry, position, and electronic nature of the substitution on the magnetic properties of the complexes. The steric effects dominate for substitution in position 3 but the electronic effects are significant for the other positions.